2023
DOI: 10.1002/nop2.1621
|View full text |Cite
|
Sign up to set email alerts
|

Serial multiple mediation of psychological empowerment and job burnout in the relationship between workplace bullying and turnover intention among Chinese novice nurses

Abstract: Aim This study aimed to examine the direct and indirect effects of workplace bullying on turnover intention using the serial multiple mediators of psychological empowerment and job burnout. Design A cross‐sectional study was conducted. Methods A convenience sample of 506 novice nurses from five Triple A hospitals in China's S province from November 2020 to February 2021 and were evaluated using online questionnaires on workplace bullying, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
2
3
1
Order By: Relevance
“…Our research showed workplace bullying was negatively related to organizational commitment and positively related to turnover intention, which supported hypothesis 1 and was consistent with the findings of Kang [ 51 ], Qi [ 52 ] and Ren [ 53 ]. Workplace bullying leads to a range of negative effects, both on the individual (physical and mental health, post-traumatic stress disorder, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…Our research showed workplace bullying was negatively related to organizational commitment and positively related to turnover intention, which supported hypothesis 1 and was consistent with the findings of Kang [ 51 ], Qi [ 52 ] and Ren [ 53 ]. Workplace bullying leads to a range of negative effects, both on the individual (physical and mental health, post-traumatic stress disorder, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…There is a bidirectional causal relationship between sleep quality and work engagement 42 . In this study, sleep quality was negatively related to work engagement, which is different from previous studies 42,43 . This may be due to the dark side of engagement.…”
Section: Discussioncontrasting
confidence: 99%
“…Our research showed a positive correlation between workplace bullying and turnover intention, which supported hypothesis 1 and was consistent with the ndings of Qi [42] and Ren [43]. Muharraq E et al [44]found that workplace bullying is one of the main reasons for high attrition and low retention rates in hospitals, and its frequency is one of the best predictors of turnover intention.…”
Section: Discussionsupporting
confidence: 91%